Evaluation of Municipal Solid Wastes Characteristics Towards Electricity Generation in Maiduguri Metropolis - Tela, B. M.; Oumarou, M. B.; Ngala, G. M.; Eljummah, A. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
This paper evaluates the characteristics of municipal solid waste (MSW) in Maiduguri metropolis for its potential use in electricity generation. Three key areas within Maiduguri were selected for the study: Area A (Northern Nigeria Flour Mills), Area B (Monday Market/Gwange area), and Area C (University of Maiduguri dumpsite). Additionally, three seasonal periods were considered - (1) rainy season, (2) cold/harmattan season, and (3) hot season. Refuse dumps in these areas were visited during each season to collect and analyze the MSW. The characteristics of the MSW were evaluated through physical analysis, which involved sifting through the waste and separating it into its major components. Further analysis included proximate and ultimate analyses conducted according to ASTM standards to determine the properties of the waste. The study revealed that the composition of refuse produced by communities in Maiduguri varies due to seasonal and behavioural changes. Wood, plastics, and grass were identified as the major physical constituents of the waste, with their proportions influenced by seasonal variations. The calorific values of MSW samples varied across the study areas, reflecting differences in population density and commercial activities. The highest calorific values were recorded in Area B during the rainy and cold seasons, with values of 19.81 MJ/kg and 15.055 MJ/kg, respectively. At the University of Maiduguri dumpsite (Area C), the calorific values of MSW samples were 7500 MJ/kg, 8420 MJ/kg, and 4500 MJ/kg for the rainy, cold, and hot seasons, respectively, resulting in an average of 6800 MJ/kg. This average is below the minimum calorific value of 7000 MJ/kg required for setting up an incineration plant with energy recovery. To enhance the energy potential of the MSW from the University of Maiduguri, supplementary fuels such as bagasse would need to be added to boost its calorific value and make it suitable for electricity generation. This study highlights the potential for MSW utilization in Maiduguri and identifies areas for improvement to optimize its energy recovery capabilities.